Skin biomarkers predict development of atopic dermatitis in infancy. Issue 3 (30th September 2022) - Rinnov, Maria Rasmussen; Halling, Anne‐Sofie; Gerner, Trine; Ravn, Nina Haarup; Knudgaard, Mette Hjorslev; Trautner, Simon; Goorden, Susan M. I.; Ghauharali‐van der Vlugt, Karen J. M.; Stet, Femke S.; Skov, Lone; Thomsen, Simon Francis; Egeberg, Alexander; et al.
Abstract: Background: There is currently no insight into biomarkers that can predict the onset of pediatric atopic dermatitis (AD). Methods: Nested in a prospective birth cohort study that examined the occurrence of physician‐diagnosed AD in 300 children, 44 random children with onset of AD in the first year of life were matched on sex and season of birth with 44 children who did not develop AD. Natural moisturizing factor (NMF), corneocyte surface protrusions, cytokines, free sphingoid bases (SBs) of different chain lengths and their ceramides were analyzed from tape strips collected at 2 months of age before onset of AD using liquid chromatography, atomic force microscopy, multiplex immunoassay, and liquid chromatography mass spectrometry, respectively. Results: Significant alterations were observed for four lipid markers, with phytosphingosine ([P]) levels being significantly lower in children who developed AD compared with children who did not (median 240 pmol/mg vs. 540 pmol/mg, p  < 0.001). The two groups of children differed in the relative amounts of SB of different chain lengths (C17, C18 and C20). Thymus‐ and activation‐regulated chemokine (TARC/CCL17) was slightly higher in children who developed AD, whereas NMF and corneocyte surface texture were similar. AD severity assessed by the eczema area and severity index (EASI) at disease onset was 4.2 (2.0;7.2). [P] had the highest prediction accuracy among the biomarkers (75.6%), whereas the combination of 5 lipid ratios gave an accuracy of 89.4%. Conclusion: This study showed that levels and SB chain length were altered in infants who later developed AD, and that TARC/CCL17 levels were higher. Abstract : This study examines whether selected skin biomarkers in stratum corneum tape strips from infants with clinically normal skin at 2 months of age are different in children who develop AD in the first year of life. Skin CCL17/TARC levels as well as lipid markers, including [P], [DS] and CER [DS] show significant alteration between children who developed AD and those who did not. ROC curve demonstrate that phytosphingosine, and to a lesser extend CCL17/TARC separate children who developed AD from those who did not.Abbreviations: AD, atopic dermatitis; CCL17/TARC, C‐C motif chemokine ligand 17/ TARC, thymus‐ and activation‐regulated chemokine; CER [DS], ceramide class with dihydrosphingosine as a sphingoid base; [DHS], dihydrosphingosine (sphinganine) [PS], phytosphingosine.